ProDesign Logic Files Effect on Apical Foramen Wear and Shape Transformation After Foraminal Enlargement - Castillo Marin, Miguel Christian [UNESP]; Abu Hasna, Amjad [UNESP]; Frozoni, Marcos; Diamantino, Mariana Gadelho Gimenez [UNESP]; Rocha, Caroline Trefiglio [UNESP]; Valera, Marcia Carneiro [UNESP]; Carvalho, Cláudio Antonio Talge [UNESP] (MDPI, 2024)
Background/Objectives: This study aimed to evaluate the effect of ProDesign Logic files 45.01 and 50.01 on apical foramen wear and shape transformation after foraminal enlargement at tooth length (TL) and 1 mm beyond. Methods: Sixty freshly extracted single-rooted lower human premolars teeth were distributed randomly into five groups (n = 12): Group 1 (40.05 WL) (control): No foraminal enlargement, Group 2 (45.01 TL): Specimens underwent foraminal enlargement with 45.01 Prodesign Logic file at TL; Group 3 (45.01 TL + 1): Specimens underwent foraminal enlargement with 45.01 Prodesign Logic file at 1 mm beyond TL; Group 4 (50.01 TL): Specimens underwent foraminal enlargement with 50.01 Prodesign Logic file at TL; Group 5 (50.01 TL + 1): Specimens underwent foraminal enlargement with 50.01 Prodesign Logic file at 1 mm beyond TL. Scanning electron microscopy was used to evaluate apical foramen variations and shape alterations. Data were analyzed by Student’s t-test, Kruskal–Wallis, and Mann–Whitney test. Results: Significant differences (p < 0.01) were observed among all tested groups compared to the control group in terms of the average worn area of the apical foramen. Foraminal enlargement led to significant shape transformation, resulting in round-shaped foramina. Conclusion: ProDesign Logic 45.01 and 50.01 files at TL causes notable wear and round-shaped foramina.
Keywords: apical foramen; foraminal enlargement; root canal preparation